2015
DOI: 10.1523/jneurosci.0302-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Fyn Kinase Regulates Microglial Neuroinflammatory Responses in Cell Culture and Animal Models of Parkinson's Disease

Abstract: Sustained neuroinflammation mediated by resident microglia is recognized as a key pathophysiological contributor to many neurodegenerative diseases, including Parkinson's disease (PD), but the key molecular signaling events regulating persistent microglial activation have yet to be clearly defined. In the present study, we examined the role of Fyn, a non-receptor tyrosine kinase, in microglial activation and neuroinflammatory mechanisms in cell culture and animal models of PD. The well-characterized inflammoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
176
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(183 citation statements)
references
References 74 publications
(6 reference statements)
6
176
1
Order By: Relevance
“…The cells were then transfected by electroporation using A-23 program of Lonza Nucleofector™ 2b devise. Detailed protocol can be found in our previous publication (Panicker et al, 2015). Post transfection, the cells were incubated for 48h followed by various treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cells were then transfected by electroporation using A-23 program of Lonza Nucleofector™ 2b devise. Detailed protocol can be found in our previous publication (Panicker et al, 2015). Post transfection, the cells were incubated for 48h followed by various treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The whole cell lysates were prepared using modified RIPA buffer as described previously (Panicker et al, 2015). To analyze the intracellular translocation, nuclear and cytosolic fractions were collected using NE/PER kit (Thermo Fisher).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, they did not explore the behavioural correlations of these findings arguing that Fyn-KO mice "were resistant to a neurotoxic lesion with 6-OHDA". Similarly, Panicker et al [40] reported attenuated DA loss in the Fyn-KO mice intrastriatally injected with 6-OHDA. The authors attributed that result to a reduced inflammatory response in Fyn-KO that may be neuroprotective.…”
Section: Discussionmentioning
confidence: 68%
“…The striatum is another location to prefer [24]. Anti-inflammation treatment based on this model is investigated for neural protection in PD process [25].…”
Section: Lps Pd Modelmentioning
confidence: 99%